2000
DOI: 10.1017/s1368980000000343
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of preschool children in informal settlement areas near Bloemfontein, South Africa

Abstract: Objective: To determine the nutritional status and household resources of preschool children. Design: A cross-sectional survey. Setting: Two informal settlement areas, Joe Slovo (JS) and JB Mafora (JBM) in Mangaung, near Bloemfontein, South Africa. Subjects: Preschool children (,72 months) of a randomly selected sample of households in JS (experimental) (n = 162) and JBM (control) (n = 186) were included. Standard methods were used to obtain household and care-giver particulars, weight and height measurements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 7 publications
6
31
0
Order By: Relevance
“…Pregnant women from the population had weights mainly in the normal to high pregnancy ranges, while their diets were inadequate in various micronutrients (Dannhauser et al, 1996a). On the other hand, the nutritional status and dietary intakes of pre-school-age black children in the Bloemfontein district (Dannhauser et al, 1996b) and of informal settlement areas near Bloemfontein (Dannhauser et al, 1998) indicated a moderate prevalence of underweight and stunting, and inadequate intake of energy and various micronutrients, while the protein was mainly of a low quality.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women from the population had weights mainly in the normal to high pregnancy ranges, while their diets were inadequate in various micronutrients (Dannhauser et al, 1996a). On the other hand, the nutritional status and dietary intakes of pre-school-age black children in the Bloemfontein district (Dannhauser et al, 1996b) and of informal settlement areas near Bloemfontein (Dannhauser et al, 1998) indicated a moderate prevalence of underweight and stunting, and inadequate intake of energy and various micronutrients, while the protein was mainly of a low quality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of black urban children increased from three 37,38,39 to six studies 1,61,68,69,70,71 (including the NFCS-I-1999 and Bt20), while studies of black rural children decreased from five 28,30,31,38,39 to a single study 1 in the last 10 years.…”
Section: Decreasing Number Of Food Intake Studies and Theses 1979-2010mentioning
confidence: 99%
“…In Southern Africa, several studies indicated vitamin B 12 (Dannhauser, Joubert, & Nel, 1996;Labadarios, 1996) and folate (Labadarios et al, 2000) deficiencies among the poor. As a result, mandatory fortification of basic foodstuffs with a number of micronutrients, including folate and vitamin B 12 , was recently promulgated (Anonymous, 2003).…”
Section: Introductionmentioning
confidence: 99%